Exploring the status of retail private drug shops in Bangladesh and action points for developing an accredited drug shop model: a facility based cross-sectional study - Ahmed, Syed Masud; Naher, Nahitun; Hossain, Tarek; Rawal, Lal Bahadur (© 2017 BioMed Central Ltd., 2018)
This article was published in the Journal of Pharmaceutical Policy and Practice [© 2017 The Author(s).] and the definitive version is available at: https://doi.org/10.1186/s40545-017-0108-8 The Journal's website is at: https://joppp.biomedcentral.com/articles/10.1186/s40545-017-0108-8